Modelling and Model Based Compensation of Non-Ideal Characteristics of Two-Level Voltage Source Inverters for Drive Control Application - Seilmeier, Markus; Wolz, Christoph; Piepenbreier, Bernhard (EDPC 2011, 2011)
In order to be able to optimize the performance of sophisticated model based AC machine control, precise models of the overall drive system are needed. This way compensation schemes for non-ideal characteristics can be derived based on the model inversion technique. Power electronic converters show the following non-ideal effects which have to be considered: turn-on delay time of the gate drive to prevent dc-link short-circuiting, non-ideal switching characteristics and forward voltages of the power electronic devices. In this paper models for these disturbances are derived and the respective compensation schemes are deduced. In constrast to conventional approaches for converter linearization, an analytic compensation law which allows considering different forward voltage-current characteristics of the diode and transistor is proposed. The effectiveness of this method is proven by means of experimental results. © 2011 IEEE.
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.modell_0
Keywords: compensation of voltage errors; forward voltage drop; inverter nonlinearity; model inversion technique; non-ideal switching characteristic; VSI modelling